2022
DOI: 10.1371/journal.pgen.1009798
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Arhgef12 and Prkci as genetic modifiers of retinal dysplasia in the Crb1rd8 mouse model

Abstract: Mutations in the apicobasal polarity gene CRB1 lead to diverse retinal diseases, such as Leber congenital amaurosis, cone-rod dystrophy, retinitis pigmentosa (with and without Coats-like vasculopathy), foveal retinoschisis, macular dystrophy, and pigmented paravenous chorioretinal atrophy. Limited correlation between disease phenotypes and CRB1 alleles, and evidence that patients sharing the same alleles often present with different disease features, suggest that genetic modifiers contribute to clinical variat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…Forward genetics approaches have been helpful in identifying genes involved in retinal degeneration 42 – 46 . Our robust and validated forward genetic pipeline (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Forward genetics approaches have been helpful in identifying genes involved in retinal degeneration 42 – 46 . Our robust and validated forward genetic pipeline (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a study conducted on mice models found out that two genetic modifiers, Arhgef12 and Prkci, play a key role in shaping the phenotype of CRB1-associated retinopathy. 81 Similar interations may also take place in the human retina, thus explaining part of the clinical variability of PPCRA.…”
Section: Familial Cases and Geneticsmentioning
confidence: 93%
“…Total RNA was isolated from postnatal day 18 (P18) retinas of B6 ( n = 6) and homozygous cpfl9 mice ( n = 6) using TRIzol (Life Technologies)/chloroform treatment as previously described ( Weatherly et al, 2022 ). RNA clean-up and DNase digestion was performed on an RNeasy spin column (Qiagen, Germantown, MD).…”
Section: Methodsmentioning
confidence: 99%